Impaired kidney function and atrial fibrillation in elderly subjects. - Deo, Rajat; Katz, Ronit; Kestenbaum, Bryan; Fried, Linda; Sarnak, Mark J; Psaty, Bruce M; Siscovick, David S; Shlipak, Michael G (J Card Fail, 2010)
BACKGROUND: Impaired kidney function is associated with increased risk for cardiovascular events. We evaluated whether kidney function is associated with atrial fibrillation (AF) risk in elderly persons. METHODS AND RESULTS: Subjects were participants in the Cardiovascular Health Study (CHS), a population-based cohort of ambulatory elderly. Measures of kidney function were cystatin C and creatinine-based estimated glomerular filtration rate (eGFR). Among the 4663 participants, 342 (7%) had AF at baseline and 579 (13%) developed incident AF during follow-up (mean 7.4 years). In unadjusted analyses, cystatin C quartiles were strongly associated with prevalent AF with a nearly 3-fold odds in the highest quartile compared with the lowest (HR=1.19, 95% CI [0.80-1.76] in quartile 2; HR=2.00, 95% CI [1.38-2.88] in quartile 3; and HR=2.87, 95% CI [2.03-4.07] in quartile 4). This increased risk for prevalent AF remained significant after multivariate adjustment. The risk for incident AF increased across cystatin C quartiles in the unadjusted analysis (HR=1.37, 95% CI [1.07-1.75] in quartile 2; HR=1.43, 95% CI [1.11-1.84] in quartile 3; and HR=1.88, 95% CI [1.47-2.41] in quartile 4); however, after multivariate adjustment, these findings were no longer significant. An estimated GFR <60 mL.min.1.73m(2) was associated with prevalent and incident AF in unadjusted, but not multivariate analyses. CONCLUSIONS: Impaired kidney function, as measured by cystatin C, is an independent marker of prevalent AF; however, neither cystatin C nor eGFR are predictors of incident AF.
Keywords: Age Factors; Aged; Aged, 80 and over; Atrial Fibrillation; Cohort Studies; Cross-Sectional Studies; Female; Follow-Up Studies; Glomerular Filtration Rate; Humans; Kidney Diseases; Kidney Function Tests; Male